KOMPETENSI SOSIAL GURU IPA SMP SE KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - Suminar, Siti; Afifah, Nurul; -, Hardianto (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study aims to determine the social competence of science teachers Se District of Pagaran TapahDarussalam Rokan Hulu. Descriptive research. This study was conducted in January 2015 at the Junior HighSchool District of Pagaran Tapah Darussalam Rokan Hulu on learning year 2014/2015. These samplesincluded 6 Junior High School science teacher District of Pagaran Tapah Darussalam. Techniques of datacollection form, questionnaire, and documentation. Data analysis technique using a Likert scale. The results ofthe study with a percentage of 83.33%, the social competence of junior high science teacher Se District ofPagaran Tapah Darussalam already implemented